Claire Launchbury and Megan C. MacDonald, editors. Urban Bridges, Global Capital(s): Trans-Mediterranean Francosphères. Liverpool UP, 2021. - Maria Vendetti (Studies in 20th & 21st Century Literature, 2022)
Review of Claire Launchbury and Megan C. MacDonald, editors. Urban Bridges, Global Capital(s): Trans-Mediterranean Francosphères. Liverpool UP, 2021. 224 pp.
Keywords: Mediterranean; Francophone; cultural capital; migration